The Toronto Empathy Questionnaire: Scale development and initial validation of a factor-analytic solution to multiple empathy measures - Spreng, R. Nathan (2009)
In order to formulate a parsimonious tool to assess empathy, we used factor analysis on a combination of self-report measures to examine consensus and developed a brief self-report measure of this common factor. The Toronto Empathy Questionnaire (TEQ) represents empathy as a primarily emotional process. In three studies, the TEQ demonstrated strong convergent validity, correlating positively with behavioral measures of social decoding, self-report measures of empathy, and negatively with a measure of Autism symptomatology. Moreover, it exhibited good internal consistency and high test-retest reliability. The TEQ is a brief, reliable, and valid instrument for the assessment of empathy.